2021
DOI: 10.1021/acs.jpcc.1c06670
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aluminum Siting in H-ZSM-5 on Reaction Barriers

Abstract: We investigate the influence of acidity and confinement for different aluminum T-site substitutions in H-ZSM-5 using reactions related to the methanol-to-olefin (MTO) process as examples. We use density functional theory at the PBE-D3 level to study all 12 different T-sites existing in the MFI framework. We find that transition-state energies vary by about 20 kJ/mol with the commonly employed T12 site having some of the lowest barriers. A large part of the energetic differences can be ascribed to differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Depending on the temperature and partial pressures, oxygenates such as water, methanol, and dimethyl ether (DME) adsorb at the BAS through the formation of a hydrogen bond. Recent studies also focus on aluminum siting as well as the effect of different Si/Al ratios. The reactivity of surface BAS, however, has rarely been studied, although with a crystal size of a few nanometers to micrometers, , zeolite particles as well as 2D zeolites offer a large surface area. At the surface, substitution of a silicon atom at a single silanol group followed by dehydration leads to a threefold coordinated aluminum atom (a structural motif not present in BAS), which generally acts as a Lewis acid site (LAS, see Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the temperature and partial pressures, oxygenates such as water, methanol, and dimethyl ether (DME) adsorb at the BAS through the formation of a hydrogen bond. Recent studies also focus on aluminum siting as well as the effect of different Si/Al ratios. The reactivity of surface BAS, however, has rarely been studied, although with a crystal size of a few nanometers to micrometers, , zeolite particles as well as 2D zeolites offer a large surface area. At the surface, substitution of a silicon atom at a single silanol group followed by dehydration leads to a threefold coordinated aluminum atom (a structural motif not present in BAS), which generally acts as a Lewis acid site (LAS, see Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…94 Our calculated intrinsic barriers using PBE+D3 alone give similar results to those calculated in the literature. 94,95 For example, using PBE+D3 we calculate an intrinsic barrier of 128 kJ mol -1 for the formation of a surface methoxy species, Smith et al calculates an intrinsic barrier of 143 kJ mol -1 , 95 whilst Kilburn et al calculates an intrinsic barrier of 119 kJ mol -1 . 94 Di Iorio et al have investigated the same dehydration reaction in a different zeolite 25 , CHA.…”
Section: Methanol Dehydration To Dimethyl Ethermentioning
confidence: 99%
“…Most commonly, Brønsted acidity is introduced by substitution of a silicon atom of the zeolite framework with an aluminum along with a proton compensating the charge difference. Both the location of the aluminum substitution in the framework and the aluminum content (i.e., the Si/Al ratio) have been shown to influence the reactivity of Brønsted acid sites. It is thus not surprising that computational studies showed that Brønsted acid catalyzed reaction barriers change by as much as 20 kJ/mol with acid site location and aluminum content. In the theoretical studies investigating proximate acid sites, the effect of an additional site is generally indirect, i.e. it changes the reactivity by modifying the potential energy surface, but it does not directly take part in the chemical reaction so that the reaction mechanism remains essentially identical. This is in contrast to Cu-substituted zeolites employed in NOx selective catalytic reduction, where mobile Cu-species were proposed to react in a cooperative fashion, thus changing the reaction mechanism when compared to a single site …”
mentioning
confidence: 99%